(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
In this article the work on judo popularization among population was carried out, mainly for athletes to achieve high results and to show results in Olympic sports. This article has studied the literature of scientists, developed a new methodology and established that the popularization of judo has been achieved.